Proteases of the neutrophil membrane represent an alternative fibrinolytic pathway to that mediated by plasmin - Adams, Susan Ann (UCT/MRC Liver Research Centre, 2017)
The cellular components of the blood, which become associated with fibrin through specific cellular adhesive processes, play a significant role in the breakdown of fibrin. Fibrinolysis by elastase and cathepsin G, enzymes present within the azurophilic granules of the neutrophil, has previously been shown. Recent studies have demonstrated neutrophil-mediated fibrinogenolysis by a membrane-associated protease which suggests that proteases connected with the neutrophil membrane might also be capable of clot dissolution. Investigations showed that neutrophil-mediated clot lysis was effected by a membrane-associated serine protease that can be dissociated by SDS-PAGE to bands that migrate to apparent molecular weights of 501 kDa, 398 kDa, 316 kDa, 245 kDa and 209 kDa. This degradation was distinct from that produced by plasmin, neutrophil lysosomal enzymes and purified human neutrophil elastase and enhanced the action of plasmin in clot solubilization. Preincubation of neutrophils with monoclonal antibodies directed against the CD 11 c/CD 18 integrin was able to significantly inhibit neutrophil membrane-dependent fibrinolytic activity. Upregulation of enzyme activity occurred following association of fibrin substrate with the cell membrane and was dependent on the activation of cellular kinases, in particular protein kinase C. Fibrin products generated by neutrophil membrane proteolytic activity were found to possess biological activity. The low molecular weight peptides effected substantial inhibition of thrombin-induced platelet aggregation while the presence of the higher molecular weight material could partially overcome platelet-induced resistance to plasmic lysis. No modulation of platelet-mediated fibrin clot retraction was observed using these same fibrin products. Neutrophil lysosomal enzyme activity was shown to further degrade the end products of plasmic fibrin degradation into low molecular weight material, followed by reassembly of higher molecular weight products in a process dependent on calcium and factor XIII. The reformed products have a similar molecular weight to those produced by plasmic lysis of fibrin, as well as a putative crosslinked site. However, the isoelectric point of these reformed products indicates they are distinctly different from plasmin-derived fibrin products. These reassembled products were recognized by a monoclonal antibody raised against D-dimer. Processing by neutrophils of the end products of plasmic fibrin degradation may have the potential for modulating the immune response as well as compromising the predictive value of tests measuring D-dimer, used as a laboratory marker of a number of thromboembolic disorders encountered in clinical practice.